Groundwater Vulnerability from Sea Water Intrusion in Coastal Area Cilacap, Indonesia - Setyawan Purnama (Faculty of Geography, Universitas Gadjah Mada, 2019)
The important issue relating to water resources is sea water intrusion (SWI) phenomena. Nowadays, the phenomena has become serious problem in the urban coastal area. Groundwater as main sources for domestic usage cannot be used again because of its salinity.Cilacap as one of urban coastal area also face the problem. In 1977 SWIwas detectedand experienced significant developmentsin 1996,This research was conducted to: (1) analyze agroundwater vulnerability to the SWI; (2) determine adistance and adepth theinterface; and (3) analyze relationship of the groundwater vulnerability to the interface depth.It was performed an analysis of the groundwater vulnerability to the SWI using the method of GALDIT, whereas the distance and depth of the interface was determined using the method of DupuitGhyben-Herzberg. The linkage analysis of the groundwater vulnerability to the depth of the actual interface was conducted by quantitative descriptively.The results showed that the distance from the shoreline was the most determined factor of the groundwater vulnerability to the SWI, the closer to the shoreline the more swallow the depth of the interface. It existed the relevance between the vulnerability level of groundwater to the SWI with the depth of actual interface. The regions with low level of vulnerability had deep interface depth, whereas the regions with moderate level of vulnerability had swallow interface depth. Nevertheless, the SWI has not yet affected the groundwater in people wells because of its depth that was not yet exceeded of 25 m.so that this depth can be used as a reference in digging wells in the research area++